Periosteal surgery - Rackard, S. M.; Bellenger, C. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Periosteal section influences bone development in many species. Long bone growth has been stimulated and limb deviations have been created and corrected by surgically manipulating the periosteum. This paper reviews clinical and experimental findings following different types of periosteal surgery on the immature long bone and considers what mechanisms may be involved in these effects.
Keywords: Periosteal incision; periosteal stripping; long bone growth